1982
DOI: 10.1055/s-2008-1055260
|View full text |Cite
|
Sign up to set email alerts
|

Okuläre Symptomatik und Leukämie im Kindesalter

Abstract: Findings in a total of 200 children suffering from leukemia were evaluated. Ocular symptoms were found in 26% of the cases. Typically, fundus hemorrhages were found in the initial stage, leukemic infiltrates in the final stage and papilledema in the meningosis leucaemica stage. In patients with ophthalmologic changes the survival time was shorter than in patients with no ocular involvement. Ophthalmological "dispensaire" treatment is generally recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Retinal hemorrhages, pre- and subretinal hemorrhages, cotton wool spots, optic disc edema, and invasion of neoplastic cells, among others, are some of the various ocular complications that have been reported for leukemia over the years [ 1 ]. However, bilateral massive vitreous hemorrhages are extremely rare [ 2 , 3 , 4 , 5 , 6 ]. Tanji et al [ 7 ] have reported adult cases with vitreous hemorrhages that were related to leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal hemorrhages, pre- and subretinal hemorrhages, cotton wool spots, optic disc edema, and invasion of neoplastic cells, among others, are some of the various ocular complications that have been reported for leukemia over the years [ 1 ]. However, bilateral massive vitreous hemorrhages are extremely rare [ 2 , 3 , 4 , 5 , 6 ]. Tanji et al [ 7 ] have reported adult cases with vitreous hemorrhages that were related to leukemia.…”
Section: Discussionmentioning
confidence: 99%